History of Education Informatization Development of China and Kazakhstan (Journal of Educational Sciences, 2021)
Informatization of education is the process of preparing people to live and work in modern information society improving quality of education through using ICT. According to world experience, policy of educational informatization started to implement in developed countries in the last century. One of them was neighboring People`s Republic of China. Having gained independence our developing country began to create and implement the first program of educational informatization to raise educational system to the world level. The purpose of article is to compare developing way of informatization policy in China and Kazakhstan. The case-study applied studying education informatization policy of two countries. This comparative case-study method based on state documents, state programms, educational laws, ICT plans and projects. The history, theoretical and practical significance of informatization policy, its penetration in educational system, development, shortcomings and achievements on the basis of comparative analysis of experience of China and Kazakhstan were considered.  Key words: Informatization policy, state programs, comparative analysis.